Single-cell transcriptional profiling revealed the protective effects of Buddleoside in sepsis-associated acute liver injury - Shi, Qingmiao; Lou, Na; Fu, Leiya; Wang, Ying; Xue, Chen; Shen, Shen; Li, Li (Frontiers in Immunology, 2026)
Sepsis-associated acute liver injury (SALI) results from dysregulated systemic immune responses, ultimately leading to liver dysfunction. Buddleoside (Bud), a naturally derived compound, has exhibited considerable therapeutic potential for liver diseases, which is attributed to its anti-inflammatory, antioxidant, and immunomodulatory effects. This study aims to evaluate the protective effects of Bud in SALI and explore its potential immunomodulatory mechanisms. In this study, SALI was induced in mice using the cecal ligation and puncture model. Biochemical analysis and histopathological evaluation demonstrated that Bud significantly attenuated hepatic inflammation and tissue damage. scRNA-seq analysis revealed that Bud inhibited endothelial cell activation, suppressed the pro-inflammatory phenotype and expression of inflammation-related genes in Ccl4+Cxcl1+ neutrophils, and decreased cytokine release and inflammation scores in specific macrophage subpopulations. These findings indicate that Bud alleviates SALI by modulating key hepatic cell populations, providing a foundation for the development of natural product-based immunotherapeutic strategies.